Answer:
see below the first three problems
Step-by-step explanation:
f(g(-2))
First, find g(-2) using function g(x). Then use that value as input for function f(x).
g(x) = -2x + 1
g(-2) = -2(-2) + 1
g(-2) = 5
f(x) = 5x
f(5) = 5(5)
f(5) = 25
f(g(-2)) = 25
g(h(3))
First, find h(3) using function h(x). Then use that value as input for function g(x).
h(x) = x^2 + 6x + 8
h(3) = 3^2 + 6(3) + 8 = 9 + 18 + 8
h(3) = 35
g(x) = -2x + 1
g(35) = -2(35) + 1 = -70 + 1
g(35) = -69
g(h(3)) = -69
f(g(3a))
First, find g(3a) using function g(x). Then use that value as input for function f(x).
g(x) = -2x + 1
g(3a) = -2(3a) + 1
g(3a) = -6a + 1
f(x) = 5x
f(-6a + 1) = 5(-6a + 1)
f(-6a + 1) = -30a + 5
f(g(3a)) = -30a + 5
Answer:
x² + 6ax + 4bx + 5a² - 5b²
Step-by-step explanation:
(x+5a+5b )(x+a-b)
x² +a x -bx +5ax + 5a² -5ab + 5bx + 5ab -5b²
x² + 6ax + 4bx + 5a² - 5b²
Answer: 0.00133m/s
Step-by-step explanation:
Given
distance crawled by the snail = 6cm = 0.06m
Time taken = 0.75minutes = 0.75*60
Time taken = 45secs
Required
constant rate of change of the snail's crawl (speed)
Speed of the snail = distance/time;
Speed of the snail = 0.06/45
Speed of the snail = 0.00133m/s
Hence the constant rate of change of the snail's crawl in m/s is 0.00133m/s